Evaluation of physicochemical properties of root-end filling materials using conventional and Micro-CT tests - Esteves Torres, Fernanda Ferrari [UNESP]; Bosso-Martelo, Roberta; Espir, Camila Galletti [UNESP]; Cirelli, Joni Augusto [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2017)
Objective: To evaluate solubility, dimensional stability, filling ability and volumetric change of root-end filling materials using conventional tests and new Micro-CT-based methods. Material and Methods: Solubility (loss of mass) after 7 and 30 days, and dimensional stability (in mm) were evaluated in accordance with Carvalho-Junior, et al.(7) (2007). The filling ability and volumetric change (in mm(3)) were evaluated by Micro-CT (Bruker-MicroCT, Kontich, Belgium) using resin models with cavities 3 mm deep and 1 mm in diameter. The cavities were filled with materials to evaluate filling ability, and then scanned by Micro-CT. After 7 and 30 days immersed in distilled water, the filled cavities were scanned again to evaluate the volumetric change. MTA Angelus (MTA), Biodentine (BIO) and zinc oxide-eugenol cement (ZOE) were evaluated. Data were submitted to analysis of variance (ANOVA) and Tukey's test with 5% significance level. Results: The results suggested correlated or complementary data between the proposed tests. At 7 days, BIO showed higher solubility and at 30 days, showed higher volumetric change in comparison with MTA (p < 0.05). With regard to volumetric change, the tested materials were similar (p > 0.05) at 7 days. At 30 days, they presented similar solubility. BIO and MTA showed higher dimensional stability than ZOE (p < 0.05). ZOE and BIO showed higher filling ability (p < 0.05). Conclusions: ZOE presented a higher dimensional change, and BIO had greater solubility after 7 days. BIO presented filling ability and dimensional stability, but greater volumetric change than MTA after 30 days. Micro-CT can provide important data on the physicochemical properties of materials complementing conventional tests.
Keywords: Endodontics; Physical properties; Calcium silicate; X-ray microtomography